Gambaran Pengetahuan Penanganan Cedera Sprain & Strain pada Siswa/I di Sekolah Menengah Pertama Pondok Pesantren Hidayatul Muslimin 2 - Fadilah, Rizki; Fradianto, Ikbal; Fauzan, Suhaimi; Mita, Mita; Fahdi, Faisal Kholid (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT The highest prevalence of injury occurs in school-age children. Injuries can be an emergency problem and can lead to very serious injuries if it is not treated properly. Furthermore, the readiness of knowledge and skills for early emergency response are very important points in order to avoid worsening the patient's condition. The purpose of this study is that to determine the overview of injury treatment knowledge of students at Islamic Junior Highscool Hidayatul Muslimin 2 Islamic Boarding School. The approach in this study used descriptive quantitative with a population of students of Islamic Junior Highscool Hidayatul Muslimin students with a research sample of 97 respondents. Meanwhile, data collection used primary data which the researcher obtained from the results of filling out the questionnaire. The result of this study shows that the level of knowledge of students at Islamic Junior Highscool Hidayatul Muslimin 2 still has a low level of knowledge that is 4.1% of the population. It is divided into three categories, good 67%, very good 16.5%, and fairly 12.4%. The conclusion of this study is that the level of knowledge of Islamic Junior Highscool Hidayatul Muslimin 2 students towards the treatment of sprain injuries and strain is still lacking in knowledge Keywords: Sprain, Strain, Injury, Knowledge Level, School Nurses.  ABSTRAK Prevalensi peristiwa cedera paling tinggi terjadi pada anak dengan usia sekolah. Cedera bisa jadi permasalahan kegawatdaruratan serta memunculkan cedera yanng sangat serius bila tidak diatasi dengan cara yang benar. Kesiapan pengetahuan serta ketrampilan kegawatdaruratan awal sebagai poin yang sagat berarti guna menghindari memburuknya keadaan penderita. Tujuan dari penelitian ini untuk mengetahui Gambaran pengetahuan penaganganan cidera oleh para siswa/I Sekolah Menengah Pertama di Pondok Pesantren Hidayatul Muslimin 2. Pendekatan dalam penelitian ini menggunakan Kuantitatif deskriptif dengan populasi Siswa/I MTS Hidayatul Muslimin 2 dengan sampel penelitian sebanyak 97 responden. Hasil penelitian ini menunjukan bahwa tingkat pengetahuan Responden di Sekolah Menengah Pertama Hidayatul Muslimin 2 masih terdapat tingkat pengetahuannya kurang yakni sebanyak 4,1% dari populasi. Pengetahuan Baik 67%, Pengetahuan Sangat baik 16,5%, Pengetahuan Cukup 12,4%. Kesimpulan dari penelitian ini penelitian ini yaitu tingkat pengetahuan Siswa/siswi Sekolah Menegah Pertama Hidayatul Muslimin 2 terhadap penanganan cedera sprain dan strain ini masih ada yang tingkat pengetahuannya kurang.   Kata Kunci: Sprain, Strain, Cedera, Pengetahuan, Remaja.